All-Cause Mortality and Cardiovascular Outcomes With Non-Vitamin K Oral Anticoagulants Versus Warfarin in Patients With Heart Failure in the Food and Drug Administration Adverse Event Reporting System. (November 2019) - von Lueder, Thomas G.; Atar, Dan; Agewall, Stefan; Jensen, Jesper K.; Hopper, Ingrid; Kotecha, Dipak; Mentz, Robert J.; Kim, Moo Hyun; Serebruany, Victor L.
Abstract : Background: Many patients with heart failure (HF) are treated with warfarin or non-vitamin K oral anticoagulants (NOACs). Randomized outcome-driven comparisons of different anticoagulant strategies in HF are lacking. Data from international, government-mandated registries may be useful in understanding the real-life use of various anticoagulants and how they are linked to outcomes. Study Question: To assess 2015 annual all-cause mortality, myocardial infarction, and stroke rates co-reported for warfarin and NOACs in subjects with and without HF in the US Food and Drug Administration Adverse Event Reporting System (FAERS) database. Study Design: We extracted and examined outcome cases in subjects with HF and on warfarin, dabigatran, rivaroxaban, apixaban, or edoxaban and stratified these according to anticoagulants. Measures and Outcomes: Annual all-cause mortality, myocardial infarction, and stroke in FAERS. Analysis Method: Odds ratio (OR) and χ 2 for oral anticoagulants from FAERS with and without HF among complete primary reports issued in 2015. Results: FAERS reported 137, 026 HF cases, with death co-reported in 42, 942 (31.3%). In total, 11, 278 (8.2%) HF patients were treated with anticoagulants, with more prescribed warfarin (n = 8260) than all NOACs combined (n = 3018). Very few reports for edoxaban were available. Warfarin consistently displayed a signal for excess adverse events compared to NOACs: OR (95% confidence interval) for the composite of mortality, myocardial infarction, and stroke were 1.91 (1.76–2.07) versus apixaban, 1.92 (1.81–2.03) versus dabigatran, 4.09 (3.38–4.37) versus rivaroxaban, and 2.64 (2.53–2.76) versus all NOACs combined (all P < 0.001). Warfarin, compared to all NOACs combined, demonstrated higher rates of all-cause mortality [OR = 2.69 (95% confidence interval, 2.49–2.90)], myocardial infarction [5.30 (4.17–6.74)], stroke [OR = 8.85 (6.61–11.84)], and ischemic stroke [OR = 12.73 (8.87–18.27); all P < 0.001]. Conclusions: Annual 2015 FAERS profiles in HF patients reveal that warfarin was numerically dominant. Warfarin was associated with higher risk of death, myocardial infarction, and stroke compared to NOACs. These observational data provide real-world insight into a potential safety benefit of NOACs over warfarin in the setting of HF.